2020
DOI: 10.1038/s41388-020-01487-6
|View full text |Cite
|
Sign up to set email alerts
|

De novo induction of lineage plasticity from human prostate luminal epithelial cells by activated AKT1 and c-Myc

Abstract: Summary Neuroendocrine prostate cancer (NEPC) is an aggressive variant of prostate cancer that either develops de novo or arises from prostate adenocarcinoma as a result of treatment resistance. Although the prostate basal cells have been shown to directly generate tumor cells with neuroendocrine features when transduced with oncogenic signaling, the identity of the cell-of-origin for de novo NEPC remains unclear. We show that the TACSTD2 hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…This hypothesis is supported by a recent study showing that high expression of TACSTD2 was associated with biochemical recurrence ( 26 ). In addition, our recent study demonstrated directly that, when transduced with activated AKT1 and c-Myc, the TACSTD2 high human prostate luminal cells possess a higher potential to undergo lineage plasticity and generate organoids containing distinct clinically relevant prostate tumor cell populations than the TACSTD2 low luminal cells ( 27 ). Prostate ductal adenocarcinoma (PDA) is rare but is the second common histological variant of prostatic carcinoma ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 96%
“…This hypothesis is supported by a recent study showing that high expression of TACSTD2 was associated with biochemical recurrence ( 26 ). In addition, our recent study demonstrated directly that, when transduced with activated AKT1 and c-Myc, the TACSTD2 high human prostate luminal cells possess a higher potential to undergo lineage plasticity and generate organoids containing distinct clinically relevant prostate tumor cell populations than the TACSTD2 low luminal cells ( 27 ). Prostate ductal adenocarcinoma (PDA) is rare but is the second common histological variant of prostatic carcinoma ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 96%
“…RB, loss), which impact their function, during CaP progression. Other important modulators of CaP cell proliferation that may be less readily recognized as cell cycle regulators include, for instance, PLK1, whose overexpression has been linked to prostate tumorigenesis (Weichert et al 2004, Deeraksa et al 2013, or MYC, whose gene amplification drives CaP/NEPC progression (Ellwood-Yen et al 2003, Kwon et al 2020. The full scope of CaP cell cycle modulators and the extent to which somatic alterations impact their expression or function, and subsequently, clinical CaP progression and treatment response, has likely not yet been determined.…”
Section: Other Molecular Events That Contribute To Regulation Of Cap Cell Proliferationmentioning
confidence: 99%
“…In this model, further differentiation to NEPC is critically dependent on p53 and RB1 loss [ 48 ]. Recently, Kwon et al showed that MYC’s overexpression, together with a constitutively activated AKT (caAKT), can drive lineage plasticity in human luminal cells–derived organoid [ 64 ]. As a plasticity consequence, MYC- and caAKT-overexpressed organoid showed heterogeneous expression of AR and neuroendocrine markers [ 64 ].…”
Section: Transcription Factors Involved In Reprogrammingmentioning
confidence: 99%
“…Recently, Kwon et al showed that MYC’s overexpression, together with a constitutively activated AKT (caAKT), can drive lineage plasticity in human luminal cells–derived organoid [ 64 ]. As a plasticity consequence, MYC- and caAKT-overexpressed organoid showed heterogeneous expression of AR and neuroendocrine markers [ 64 ]. Nevertheless, it remains to be determined if the de-differentiation can also occur in the absence of MYC.…”
Section: Transcription Factors Involved In Reprogrammingmentioning
confidence: 99%